Implementasi Internet of Things Untuk Menjaga Kelembaban Udara Pada Budidaya Jamur - Aligia Ricky Agusta; Justinus Andjarwirawan; Resmana Lim (Jurnal Infra, 2019)
Internet of things in a broad sense makes everything in the world connected to the internet that is connected continuously. The internet of things can control, send data, and so on that uses the internet so that it can be done remotely without knowing distance. The current implementation of air humidity control is still done by feeling directly through human skin and then will do the fogging if the humidity is felt lacking. With the internet of things, it can be implemented to control air humidity remotely through the website. To make the air humidity controller needed a tool such as humidity sensor and air temperature SHT11, microcontroller, relay, sprayer. The website uses the website for the interaction of humidity and air temperature sensors, microcontrollers, or other tools through the internet. This website is used to facilitate users to access the internet anywhere and use devices that are able to open websites. Website created using php. The microcontroller used is WeMos D1 R2 which has ESP8266 in it. The final result of the development of this air humidity controller is that the microcontroller can send data from the sensor to the web server, air humidity that matches the setpoint. Users can view daily humidity and air temperature charts.